BIOACCUMULATION OF METAL IN FRESHWATER PELECYPOD MOLLUSCS UNDER EXPERIMENTAL CONDITION - WAYKAR BHALACHANDRA; SATISH SHINDE; GAJANAN DESHMUKH (The Bioscan, 2011)
The objective of the present study was to find the most appropriate sentinel bivalve species for metal pollution biomonitoring programme in the freshwater ecosystem. The freshwater bivalves namely, Parreysia cylindrica, Corbicula striatella, Parreysia corrugata, Lamellidens corrianus, Lamellidens marginalis and Indonaia caeruleus were separately exposed to chronic concentration of arsenic (0.1719 ppm), cadmium (0.1411 ppm), copper (0.033 ppm), lead (1.50ppm), mercury (0.0443 ppm) and zinc (1.8589 ppm) up to 30 days in laboratory. It was found that the freshwater bivalve, Lamellidens corrianus showed the highest concentration of arsenic (37.9μg) and lead (1235.4μg), Lamellidens marginalis showed highest concentration of copper (826.7μg) and mercury (5.87μg), while Parreysia cylindrica had highest concentration of cadmium (182.62μg) and Corbicula striatella showed highest concentration of zinc (4139.2μg) per gm dry tissues. The bioconcentration factor (BCF) was high for arsenic and lead in Lamellidens corrianus, copper and mercury in Lamellidens marginalis, cadmium in Parreysia cylindrica and zinc in Corbicula striatella. Therefore Lamellidens corrianus is proposed as sentinel organism for the biomonitoring of arsenic and lead, Lamellidens marginalis for copper and mercury, Parreysia cylindrica for cadmium and Corbicula striatella for zinc in freshwater ecosystem.